The Oxford handbook of management in emerging markets - Grosse, Robert E.; Meyer, Klaus, 1964- (New York : Oxford University Press, 2018)
Emerging Markets are the primary source of growth for business in the 21st century. This makes an understanding of managing businesses in emerging markets a fundamental building block for competing in today's global economy. This book's approach is to identify key elements of the business systems and competition in emerging markets around the world, and then to look at competitive strategies of local and multinational companies going into and coming out of these countries. Specific focus is offered on a selection of countries/regions.
Introduction to Managing in Emerging Markets / Klaus E. Meyer, Robert Grosse -- Consumer Behavior in Emerging Markets / Raquel Castaño, David Flores -- Examining Base of the Pyramid (BoP) Venture Success through the Mutual Value CARD Approach / Krzysztof Dembek, Nagaraj Sivasubramaniam -- Regulatory Institutions and Multinational Companies in Emerging Markets / Farok J. Contractor -- Corporate Political Ties in Emerging Markets / Pei Sun -- Adjustment of MNE Geographic Market Strategy in Responding to the Rise of Local Competitors in an Emerging Market / J.T. Li, Zhenzhen Xie -- Global Production Networks, Territoriality, and Political Authority / Stephen J. Kobrin -- Innovation in Emerging Markets / George S. Yip, Shameen Prashantham -- Spillovers from FDI in Emerging Market Economies / Sumon Kumar Bhaumik, Nigel Driffield, Meng Song, Priit Vahter -- Conceptual Approaches to Managing in Emerging Markets / Robert Grosse, Klaus E. Meyer -- Risk Management for Companies Operating in Emerging Markets / Donald Lessard -- Entrepreneurship in Emerging Markets / Saul Estrin, Tomasz Mickiewicz, Ute Stephan, Mike Wright -- Innovation and Internationalization of SMEs in Emerging Markets / John Child -- Family Business in Emerging Markets / Rodrigo Basco -- The Economic and Sociological Approaches to Research on Business Groups in Emerging Markets / Chi‐Nien Chung, Rose Xiaowei Luo -- State-Owned Multinationals in International Competition / Aldo Musacchio, Felipe Monteiro, Sergio G. Lazzarini -- Local Firms Within Global Value Chains: From Local Assembler to Value Partner / Shameen Prashantham, George S. Yip -- Emerging Market Multinationals in Advanced Economies / Lin Cui, Preet S. Aulakh -- Investments by Emerging-Market Multinationals in Other Emerging Markets / Jing Li, Daniel Shapiro -- Human Resource Management in Emerging Markets / Dana Minbaeva -- International Business and Emer
Includes bibliographical references and index.
Description based on online resource; title from home page (viewed on February 5, 2019).
Keywords: Management -- Developing countries; Marketing -- Developing countries -- Management; Small business -- Developing countries -- Management